The Impacts Of Structure, Climate And Selfefficacy On Stress: A Malaysian Survey - Mohd. Nasurdin, Aizzat; T. Ramayah , T. Ramayah; Yeoh , Chee Beng (Asian Academy of Management (AAM), 2009)
This study examines the impacts of organisational structure (formalisation and centralisation) and organisational climate in predicting job stress in a non-Western environment. It also explores the moderating effects of self-efficacy in the proposed relationships. A total of 151 securities sales personnel in Malaysia were sampled for this study. The findings indicated a positive relationship between both structural variables and stress. The organisational climate dimensions were found to be unrelated to stress. The role of self-efficacy as a moderator in the hypothesised relationships had limited support. Implications of this work and directions for future research are discussed.